A Scientometric Analysis of Construction Bidding Research Activities - Rashidi, Amirreza; Tamošaitienė, Jolanta; Ravanshadnia, Mehdi; Sarvari, Hadi (Buildings (Basel), 2023)
Bidding is the process in which a contractor submits a tender to the owner of a construction project to undertake its execution. This enables companies to properly employ required contractors. This paper investigates the trends of research conducted on construction bidding from 1975 to 2022 through a scientometric analysis from different viewpoints. A total of 299 relevant articles published in 191 journals were collected from the Web of Science database and analyzed by HistCite and CiteSpace software. The top journals, articles, institutes, and authors that contributed to bidding studies were ranked. The trends of published articles and contributions from different countries on the subject were examined. Moreover, the co-occurrence network, strongest burst detection, trends of the top keywords, and cluster analysis were determined. This review creates an in-depth insight into the content, enabling researchers to understand the existing body of knowledge and to trace a practical guideline for future studies.